BEYOND THE MAKEUP: UNCOVERING FACTORS BEHIND COSMETIC PURCHASE DECISIONS - Avida Zahra; Zakky Fahma Auliya (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
This study investigates at the important elements that impact consumers' purchasing decisions for Instaperfect, a high-end local cosmetic company in Indonesia. The study analyzes the issue of contradictory past findings on the impact of e-WOM, perceived value, and consumer trust on purchase decisions, notably in the luxury cosmetics category. The goal of this study is to look at how these three variables influence consumer decisions at the same time, utilizing the Theory of Planned Behavior (TPB) as a framework. An online questionnaire was used to collect data from 231 members of the OHMYBEAUTYBANK community, using a quantitative research approach. Structural Equation Modeling (SEM-PLS) was used to evaluate the measurement model and the structural connections among variables. The findings reveal that e-WOM does not significantly influence purchase decisions for Instaperfect cosmetics. In contrast, perceived value and consumer trust have positive and significant effects on purchase decisions, indicating that consumers tend to prioritize product benefits, worthiness relative to price, and brand reliability over online reviews. These results suggest that perceived value and trust are more dominant drivers of consumer behavior in the premium cosmetics category. The study contributes by providing empirical evidence on TPB-based factors influencing cosmetic purchase decisions within Indonesian premium local brands and by involving a targeted beauty community as the research sample. Practically, the findings suggest that brands should strengthen product value and consumer trust through quality consistency, transparent communication, and a solid brand identity. Future research may broaden the sample and explore additional variables such as brand image, perceived quality, or brand experience to deepen insights into consumer behavior.